2013
DOI: 10.1103/physrevlett.110.122501
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Tensor Force onβDecay of Magic and Semimagic Nuclei

Abstract: The effect of the tensor force on β decay is studied in the framework of the proton-neutron random phase approximation with the Skyrme force. The investigation is performed for even-even semimagic and magic nuclei, (34)Si, (68,78)Ni, and (132)Sn. The tensor correlation induces strong impact on the low-lying Gamow-Teller state. In particular, it improves the β-decay half-lives. Q and ft values are also investigated and compared with experimental data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 36 publications
2
31
0
2
Order By: Relevance
“…Not only on nuclear ground states [9,26], but also in nuclear excitations [14,15,31,32] and β decay [19,36] there is a common understanding of the nonrelativistic and relativistic models, for instance, the SHF and RHF models. Both indeed share the success due to the presence of the tensor force component which is added to the Skyrme EDF, or naturally involved in the RHF one.…”
Section: Nuclear Tensor Interactions In a Covariant Energy Densitmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only on nuclear ground states [9,26], but also in nuclear excitations [14,15,31,32] and β decay [19,36] there is a common understanding of the nonrelativistic and relativistic models, for instance, the SHF and RHF models. Both indeed share the success due to the presence of the tensor force component which is added to the Skyrme EDF, or naturally involved in the RHF one.…”
Section: Nuclear Tensor Interactions In a Covariant Energy Densitmentioning
confidence: 99%
“…In recent years, substantial impacts due to the nature of the tensor force were recognized in the extensions of the nuclear chart from traditional stable nuclei to exotic ones [8][9][10][11][12][13]. Moreover, impressive progress associated with the nuclear tensor force was also achieved in describing the nuclear excitations [14][15][16][17][18] and decay modes [19]. For instance, within the Skyrme Hartree-Fock (SHF) plus random phase approximation (RPA) scheme, it was found that the tensor force components play a crucial role in understanding the Gamow-Teller (GT) transition [14], charge-exchange spin-dipole (SD) excitations [15], the non-charge-exchange multipole responses [16] and the β decay of magic and semimagic nuclei [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Making use of the finite-rank separable approximation (FRSA) [36][37][38] for the p-h interaction enables us to perform CERPA calculations in very large configuration spaces. Although it is well known that the tensor interaction influences also the description of the β − -decay half-lives [39], in the present study the tensor force is neglected in order to focus on the impact of the SPEM.…”
Section: Calculations Of β-Decay Ratesmentioning
confidence: 99%
“…In recent years, the nuclear tensor force was shown to play an essential role in determining the shell evolution from the stable to exotic nuclear systems, either by the nonrelativistic or relativistic calculations [8,10,[21][22][23][24][25], although some suspicions remain due to the fact that the particle-vibration couplings were not included [26]. Furthermore, the inclusion of the nuclear tensor force also had a substantial impact on the understanding of the nature of nuclear excitations and decay modes [12,14,27,28]. For the density-dependent behavior of nuclear symmetry energy-the * longwh@lzu.edu.cn key quantity to understanding the nuclear equation of state (EoS) and relevant astrophysical processes [29,30]-the tensor effects have also been revealed to be among the physics responsible for the uncertainty of the symmetry energy at supranuclear densities [17,18].…”
Section: Introductionmentioning
confidence: 98%